Exploring Substantive Representation Role of Lady Councilors in Local Governance of South Punjab - Amna Mushtaq; Prof. Dr. Khalil Ahmed (Journal of Management Practices, Humanities and Social Sciences, 2022)
This study analyzes women’s substantive representation in local governance of South Punjab, Pakistan. Substantive representation is believed to empower women against structural context. However, gendered representation in local governance has implications for women’s political participation and empowerment. The first objective was to see women’s substantive representation against the backdrop of structural settings of local governance in South Punjab, Pakistan. The second objective was to analyze women’s political experiences with regard to their substantive representation in local governance. Qualitative approach was used to analyze social and political obstacles confronting women lay councilors with regard to their substantive representation in local governance. In-depth interviews were conducted from 15 lady councilors of Multan District situated in South Punjab, Pakistan. Interview guide was used as a tool for data collection. Thematic discourse analysis was carried out to analyze political experiences. Women substantive representation is undistinguishable in local governance system of Punjab, Pakistan. Local political structures increased resources of women’s right awareness, promoting women’s interaction social platform in the form of social women based political lobbing, and coordination among lady councilors for promoting their social and political rights . Their substantive representation also increases the chances of opportunities for empowering themselves socially, politically, academically and economically.